2006
DOI: 10.1128/jvi.01915-05
|View full text |Cite
|
Sign up to set email alerts
|

The Self Primer of the Long Terminal Repeat Retrotransposon Tf1 Is Not Removed during Reverse Transcription

Abstract: The long terminal repeat retrotransposon Tf1 of Schizosaccharomyces pombe uses a unique mechanism of self priming to initiate reverse transcription. Instead of using a tRNA, Tf1 primes minus-strand synthesis with an 11-nucleotide RNA removed from the 5 end of its own transcript. We tested whether the self primer of Tf1 was similar to tRNA primers in being removed from the cDNA by RNase H. Our analysis of Tf1 cDNA extracted from virus-like particles revealed the surprising observation that the dominant species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…This was tested using the homologous recombination assay, as described previously (Atwood-Moore et al 2006), which measures the amount of Tf1 cDNA in the nucleus by detecting homologous recombination between Tf1 cDNA and the Tf1 donor plasmid. In this assay, the neo gene within the Tf1 transposon is disrupted by an AI that renders it inactive until the intron is removed by splicing during transcription.…”
Section: Sap1 Promotes Tf1 Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…This was tested using the homologous recombination assay, as described previously (Atwood-Moore et al 2006), which measures the amount of Tf1 cDNA in the nucleus by detecting homologous recombination between Tf1 cDNA and the Tf1 donor plasmid. In this assay, the neo gene within the Tf1 transposon is disrupted by an AI that renders it inactive until the intron is removed by splicing during transcription.…”
Section: Sap1 Promotes Tf1 Integrationmentioning
confidence: 99%
“…Preparation and analysis of nucleic acid cDNA preparations were performed as described previously (Atwood-Moore et al 2006). In brief, total DNA was extracted from cells grown for 36 hr using glass beads and phenol.…”
Section: Two-hybrid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since in Tf1 the cellular tRNA is replaced by the SP, one could expect by analogy that the SP would also be removed by the RT-associated RNase H activity. Surprisingly, there is evidence that only a small fraction of the in vivo-generated Tf1 cDNA has the SP removed (2). This finding highlights another potentially exclusive property of the reverse transcription process of Tf1.…”
mentioning
confidence: 79%
“…Sequence analyses of terminal sequences of the in vivo generated Tf1 cDNAs have also suggested that there are distinct features of this retroelement’s reverse transcription, such as the inefficient removal of the RNA self‐primer [11]. Based on these terminal sequences, substantial sequence additions, beyond the correct and conserved 3′‐end CA dinucleotides, were identified [11,12]. This may imply that Tf1 RT has an exceptional capacity to add non‐templated dNTPs to the cDNA ends.…”
Section: Introductionmentioning
confidence: 99%